2018
DOI: 10.3389/fneur.2018.00836
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings in a Multicenter MRI Study of Mild TBI

Abstract: Background: Uncertainty continues to surround mild traumatic brain injury (mTBI) diagnosis, symptoms, prognosis, and outcome due in part to a lack of objective biomarkers of injury and recovery. As mTBI gains recognition as a serious public health epidemic, there is need to identify risk factors, diagnostic tools, and imaging biomarkers to help guide diagnosis and management.Methods: One hundred and eleven patients (15–50 years old) were enrolled acutely after mTBI and followed with up to four standardized ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…WMH were defined as hyperintense lesions on FLAIR, without hypointense lesions on SWI, which persisted unchanged across all time points on MRI. First, in line with another study, 44 we found no difference in the frequency of non-traumatic WMH between the mTBI group and the controls, as expected based on these lesions considered not to be of traumatic origin.…”
Section: Discussionsupporting
confidence: 92%
“…WMH were defined as hyperintense lesions on FLAIR, without hypointense lesions on SWI, which persisted unchanged across all time points on MRI. First, in line with another study, 44 we found no difference in the frequency of non-traumatic WMH between the mTBI group and the controls, as expected based on these lesions considered not to be of traumatic origin.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, pupil dilation velocity, percentage change in pupil size, and maximum constriction velocity parameters showed statically significant alterations after a mild traumatic brain injury (mTBI), findings that have already been confirmed by Ciuffreda et al 3 However, the changes of these parameters could not be interpreted to be due only to anatomical changes or neuron pathway dysfunction. As already described by Shetty et al, 4 about 27% of the patients after an mTBI develop white matter changes. Of the neuropsychological assessments used, the 5-and 6-Digit Backward Recall, the modified Balance Error Scoring System (BESS), and the Immediate 5-Word Recall significantly improved longitudinally in mTBI subjects and facilitated differentiation between the mTBI subjects and controls.…”
supporting
confidence: 58%
“…We chose strict inclusion criteria investigating mTBI patients with negative routine brain scans that are often underdiagnosed yet still exhibit posttraumatic symptoms [37]. Early diagnosis of those presumably mildly braininjured patients at risk for long-term consequences is critically relevant as longitudinal follow-up studies underline continued symptoms, including chronic fatigue, psychiatric disorders, and unsatisfied quality of life in one third of patients [38][39][40][41]. A recent meta-analysis revealed that MRS might have limitations for use in mTBI patients [21], which is contradictory to our findings possibly due to a greater heterogeneity of their study population.…”
Section: Discussionmentioning
confidence: 99%